2014
DOI: 10.3390/ijms151121155
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Alleviates GA-Induced Programmed Cell Death in Wheat Aleurone Layers via the Regulation of H2O2 Production and Heme Oxygenase-1 Expression

Abstract: Heme oxygenase-1 (HO-1) and hydrogen peroxide (H2O2) are key signaling molecules that are produced in response to various environmental stimuli. Here, we demonstrate that cobalt is able to delay gibberellic acid (GA)-induced programmed cell death (PCD) in wheat aleurone layers. A similar response was observed when samples were pretreated with carbon monoxide (CO) or bilirubin (BR), two end-products of HO catalysis. We further observed that increased HO-1 expression played a role in the cobalt-induced alleviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
(123 reference statements)
0
5
0
Order By: Relevance
“…In addition, haematin blocked the decrease of GA-induced ascorbate peroxidase (APX) and CAT activities, and then resulted in the decrease of H 2 O 2 level, and these effects were reversed by HO-1 inhibitor ZnPPIX ( Wu et al, 2011 ). The up-regulation of HO-1 would contribute to the capability of HO, act as a potent antioxidant enzyme, eliminating ROS and protecting cells from oxidative stress in wheat aleurone layers ( Wu et al, 2011 , 2014 ), which has previously been confirmed in plants ( Noriega et al, 2004 ; Han et al, 2008 ). The present study showed that the up-regulation of HO contributed to the delay in PCD in rice aleurone layers induced by GA under drought stress, the similar results were obtained by Wu et al (2011 , 2014 ).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In addition, haematin blocked the decrease of GA-induced ascorbate peroxidase (APX) and CAT activities, and then resulted in the decrease of H 2 O 2 level, and these effects were reversed by HO-1 inhibitor ZnPPIX ( Wu et al, 2011 ). The up-regulation of HO-1 would contribute to the capability of HO, act as a potent antioxidant enzyme, eliminating ROS and protecting cells from oxidative stress in wheat aleurone layers ( Wu et al, 2011 , 2014 ), which has previously been confirmed in plants ( Noriega et al, 2004 ; Han et al, 2008 ). The present study showed that the up-regulation of HO contributed to the delay in PCD in rice aleurone layers induced by GA under drought stress, the similar results were obtained by Wu et al (2011 , 2014 ).…”
Section: Discussionmentioning
confidence: 62%
“…The up-regulation of HO-1 would contribute to the capability of HO, act as a potent antioxidant enzyme, eliminating ROS and protecting cells from oxidative stress in wheat aleurone layers ( Wu et al, 2011 , 2014 ), which has previously been confirmed in plants ( Noriega et al, 2004 ; Han et al, 2008 ). The present study showed that the up-regulation of HO contributed to the delay in PCD in rice aleurone layers induced by GA under drought stress, the similar results were obtained by Wu et al (2011 , 2014 ). Above mentioned results revealed that HO-1 function in the PCD of cereal aleurone layers is dependent on enhancing the activities of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Nevertheless, H 2 O 2 releases embryo dormancy in barley by activating GA signaling and synthesis rather than the repression of ABA signaling ( Bahin et al, 2011 ). GA biosynthesizes in embryo during the germination and induces H 2 O 2 production in wheat aleurone cells; H 2 O 2 subsequently acts as a signal molecule to antagonize ABA signaling ( Wu et al, 2014 ). Additional evidence has suggested that GA induces the germination of dormant caryopses by regulating the level of ABA and the ROS-antioxidant status ( Cembrowska-Lech et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, the beneficial effect of exogenous H 2 O 2 in rice aleurone layers is supported by some studies that showed, for example, that exogenous application of H 2 O 2 enhanced the activities of the antioxidant enzymes SOD, CAT, and APX, and also reduced the content of MDA in wheat and maize subjected to salt stress ( Li et al, 2011 ; Gondim et al, 2012 ), and that endogenous H 2 O 2 levels were not enhanced by the addition of a low concentration H 2 O 2 in seedlings for 24 or 48 h prior to drought stress or salt stress ( Fedina et al, 2009 ; Hossain and Fujita, 2013 ). Subsequent experiments revealed that the HO-1 inducer hematin can mimic the effects of the antioxidants AsA and DMTU on down-regulating endogenous H 2 O 2 levels ( Figure 2 ), indicating that HO-1 may act as a potent antioxidative enzyme in the protection of cells from oxidative stress ( Wu et al, 2011 , 2014 ). Our experiments also revealed that DPI, an NADPH synthase inhibitor, significantly inhibited H 2 O 2 levels ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 98%